PENGARUH MORAL KARYAWAN DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Sucahya, I Wayan; Suana, I Wayan (E-Jurnal Manajemen; Vol 5 No 11 (2016), 2016)
This study aimed to determine the effect of employee morale and organizational commitment on organizational citizenship behavior, and determine the influence of employee morale and organizational commitment together to organizational citizenship behavior. This research includes studies explanation or explanatory research. The population in this study were all employees of the Licensing Services Agency One Stop And Investment (BPPTSP & PM) Denpasar. The samples were analyzed by 67 respondents using methods of sampling jenuh.Metode data collection was conducted through a questionnaire. Data analysis technique used is multiple regression analysis. Results of the analysis showed that the morale of employees and organizational commitment have significant positive effect on organizational citizenship behavior on employee Licensing Services Agency One Stop Investment (BPPTSP & PM) Denpasar. Employee morale and organizational commitment simultaneous positive and significant impact on organizational citizenship behavior on employee Licensing Services Agency One Stop Investment (BPPTSP & PM) Denpasar
Keywords: employee morale, organizational commitment, organizational citizenship behavior